A hydrophilic gadolinium hydroxide nanosheet and preparation method thereof
By treating gadolinium oxide nanoparticles with silane coupling agents and cation exchange resins, layered hydrophilic gadolinium hydroxide nanosheets were prepared, solving the problems of slow reaction rate, non-uniform size, and easy agglomeration in existing technologies, and realizing efficient and low-cost nanoparticle preparation.
Patent Information
- Application Number
- CN202310516576.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-05-09
AI Technical Summary
Existing technologies for preparing gadolinium hydroxide nanoparticles suffer from problems such as slow reaction rate, non-uniform size, easy agglomeration, low yield, and numerous byproducts, especially for one-dimensional gadolinium hydroxide nanoparticles prepared under hydrothermal conditions.
By surface modification of gadolinium oxide nanoparticles with silane coupling agents and reaction with cation exchange resin, hydrophilic gadolinium hydroxide nanosheets with a layered structure were prepared. The gadolinium oxide nanoparticles were then encapsulated with silane coupling agents and treated in cation exchange resin to form an organic-inorganic combined structure.
The prepared hydrophilic gadolinium hydroxide nanosheets have uniform size distribution, stable crystal structure, good dispersibility, and the synthesis process is simple, with low equipment requirements, few by-products, and high yield. They also have good thermal conductivity and flexibility.
Smart Images

Figure CN116514154B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional material preparation, and in particular to a hydrophilic gadolinium hydroxide nanosheet and a preparation method thereof. Background Art
[0002] Rare earth oxides refer to compounds composed of rare earth elements. In recent years, rare earth oxide nanomaterials have been widely used in the preparation of catalysts, optical glass, magnetic materials, electronic materials and other fields due to their good chemical stability, strong corrosion resistance and excellent thermal stability. Among various types of rare earth materials, gadolinium (Gd) exhibits important functional properties related to structure. Gadolinium is a member of the lanthanide series and belongs to the inner transition element. Due to its special valence electron structure, it can largely make up for the "weak absorption zone" of the outer electron layer K layer, making it widely used in optics, magnetism and nuclear radiation. For example, gadolinium has the advantage of low phonon energy and is an excellent fluorescent matrix material; it has the largest neutron absorption cross section among rare earth elements and can be used as a control rod material for nuclear reactors; it has a strong absorption effect on X-rays and is one of the potential candidate materials for magnetic resonance imaging (MRI) contrast agents. It can be seen that gadolinium has a wide range of application prospects.
[0003] Due to the excellent physical and chemical properties of rare earth elements, the synthesis and properties of rare earth elements have also received attention in recent years. The performance of rare earth elements is related to the structure and size of the particles themselves, as well as the morphology of the particles (such as rod-shaped, spherical, multi-layer, lamellar, etc.). There are many methods for preparing gadolinium hydroxide nanoparticles. Among them, the most common method is to prepare gadolinium hydroxide with a particle-like morphology by hydrothermal treatment of gadolinium oxide under hydrothermal conditions. However, the reaction speed is slow, and the one-dimensional structure of gadolinium hydroxide obtained has a large size difference and is easy to agglomerate.
[0004] Fabrication of gadolinium hydroxide nanoparticles using ion-exchange resin and their MRI property, by adding alkaline anion exchange resin (BAER) to the aqueous solution of Gd(NO3)3, aging at room temperature for 12-24h, using the anions obtained from the Gd(NO3)3 aqueous solution to react with the OH in the anion exchange resin -The exchange was carried out and kept in BAERs, and by increasing the pH value, gadolinium hydroxide nanoparticles with a needle-like structure were prepared (Anopaque solution was prepared by adding basic anion exchange resin (BAER) to a Gd(NO3)3 aqueous solution at room temperature and aging the solution for 12-24h; the solution became basic because of the exchange of H2O with OH-. The particles in the opaque solution have an anedle structure, and their crystal structure is washexagonal Gd(OH)3). Due to the different final pH values, the crystal form of the obtained gadolinium hydroxide nanoparticles changes, resulting in a large difference in their morphology. In addition, if the stirring is not in place during the preparation process, there will be more by-products and a lower yield. Summary of the invention
[0005] In order to overcome the disadvantages of the above-mentioned prior art, the object of the present invention is to provide a hydrophilic gadolinium hydroxide nanosheet and a preparation method thereof. The surface of gadolinium oxide nanoparticles is modified by using a silane coupling agent, and then a cation exchange resin is used to react with the surface-modified gadolinium oxide nanoparticles to obtain a hydrophilic gadolinium hydroxide nanosheet with a lamellar structure. The hydrophilic gadolinium hydroxide nanosheet has uniform size distribution, stable crystal structure, good dispersibility, simple preparation process, mild reaction conditions, less by-products, high yield, low equipment requirements and short preparation cycle.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0007] A hydrophilic gadolinium hydroxide nanosheet comprises, by mass percentage, 32.0%-40.0% of gadolinium oxide nanoparticles and 60.0%-68.0% of a silane coupling agent.
[0008] A method for preparing hydrophilic gadolinium hydroxide nanosheets comprises the following steps:
[0009] Step 1: mixing gadolinium oxide nanoparticles with water in a mass ratio of 1:(20-30) to obtain a milky white dispersion A;
[0010] Step 2: diluting a silane coupling agent in deionized water to obtain a silane coupling agent solution, maintaining the pH of the silane coupling agent solution in the range of 6-7.5, adding the milky white dispersion A prepared in step 1 to the silane coupling agent solution, in a mass ratio of silane coupling agent: deionized water: milky white dispersion A = 1: (6.8-8.4): (13.2-15.5), at a temperature of 20-30° C. and a rotation speed of 300-600 rpm, magnetically stirring for 12-48 hours, so that the silane coupling agent fully wraps the gadolinium oxide nanoparticles to obtain liquid B;
[0011] Step 3: Transfer the B solution prepared in step 2 to a dialysis bag with a molecular weight ≥ 3000, dialyze for 12-48 hours, change the water 4-8 times in the middle, transfer the dialyzed B solution to the pretreated cation exchange resin, and the mass ratio of dialyzed B solution: cation exchange resin = 1: (0.58-0.78), at a temperature of 20-30° C. and a rotation speed of 300-600 rpm, stir magnetically for 12-48 hours, filter out the cation exchange resin, and obtain clarified hydrophilic gadolinium hydroxide nanosheets.
[0012] The cation exchange resin pretreated in step 3 is pretreated in the following process:
[0013] Weigh the cation exchange resin, clean the impurities with deionized water, immerse it in an acid solution with a mass percentage concentration of 4%-6% and stir it for 12-24h, and calculate the mass ratio of cation exchange resin: acid solution = 1: (0.71-1.21) to obtain the pretreated cation exchange resin, that is, convert the Na type cation exchange resin into the H type cation exchange resin.
[0014] The cation exchange resin pretreated in step 3 is preferably 732 strong acid styrene cation exchange resin.
[0015] The silane coupling agent in the step 2 is preferably 3-aminopropyltriethoxysilane (KH-550) or γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560) or 3-(trisilyl)-propanesulfonic acid (SIT8378.3).
[0016] In the step 2, the pH of the solution is maintained in the range of 6-7.5, preferably using 0.5-2 mol / L NaOH solution, 0.5-2 mol / L KOH solution or 0.5-2 mol / L NH3·H2O solution to adjust the pH.
[0017] The acid solution is preferably a hydrochloric acid solution, a sulfuric acid solution or a nitric acid solution.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] 1. Compared with the prior art, the present invention can prepare a hydrophilic gadolinium hydroxide nanosheet with a lamellar structure. Such hydrophilic gadolinium hydroxide nanosheets are connected by van der Waals bonds. Therefore, compared with other structures, the hydrophilic gadolinium hydroxide nanosheet prepared by the present invention has a dense structure. Since the lamellar structures can slide against each other and absorb part of the external force, they have certain flexibility and compressive resistance. In addition, this interlayer arrangement structure has a good thermal conductivity mechanism and excellent thermal conductivity.
[0020] 2. The present invention uses a silane coupling agent to modify the gadolinium oxide nanoparticles, so that the silane coupling agent and the surface functional groups of the nanoparticles undergo a chemical bonding reaction, and then after being treated with a cation exchange resin, organic functional groups will exist on the surface. The synergistic effect of the inorganic component and the organic component can effectively improve the interface compatibility between the inorganic network structure and other composite materials, so that the nanoparticles are dispersed more evenly in the resin matrix.
[0021] 3. The present invention can use any of various silane coupling agents, and the equipment and raw material requirements are simple. The morphology of the gadolinium oxide nanoparticles after coating and modification can be controlled by selecting different types of silane coupling agents and changing the time they are in the cation exchange resin to obtain hydrophilic gadolinium hydroxide nanosheets with different crystal forms.
[0022] 4. Since the raw materials of the present invention only contain gadolinium oxide nanoparticles and a silane coupling agent and the type of the silane coupling agent is not limited, the synthesis process equipment is simple and the reaction can be carried out at room temperature. Compared with the hydrothermal method for synthesizing gadolinium hydroxide, this method has the characteristics of simple synthesis process, low equipment requirements, easy operation, mild reaction conditions, less by-products, higher yield and relatively short synthesis cycle.
[0023] 5. In the present invention, an organic adsorption layer is formed on the surface of the inorganic gadolinium oxide nanoparticles. This organic-inorganic combined structure and the silanol formed after the hydrolysis of the siloxy groups on the surface of the silane coupling agent make the prepared hydrophilic gadolinium hydroxide nanosheets have good hydrophilicity, uniform size distribution, and good dispersion stability.
[0024] 6. Compared with other structures, hydrophilic gadolinium hydroxide nanosheets with lamellar structure have higher specific surface area, thinner thickness and uniform size. Therefore, they have more advantages than other shapes in some application fields, such as preparation of nanomaterial composites, catalysts, and optical doping.
[0025] 7. The cation exchange resin in the present invention converts the Na-type cation exchange resin into the H-type cation exchange resin, so that it can adsorb a large amount of sodium ions present in the B solution, reduce the generation of by-products, and improve the yield.
[0026] 8. The silane coupling agent contains a large number of hydrolyzable groups. During coupling, these alkoxy groups can be hydrolyzed into silanols, thereby increasing the hydrophilicity of the gadolinium oxide nanoparticles. In addition, since 3-aminopropyltriethoxysilane (KH-550) contains amino groups, the hydrophilicity of the prepared gadolinium hydroxide nanosheets is significantly increased.
[0027] In summary, the present invention uses a silane coupling agent to perform surface modification on gadolinium oxide nanoparticles, and then uses a cation exchange resin to react with the surface-modified gadolinium oxide nanoparticles to prepare hydrophilic gadolinium hydroxide nanosheets with a lamellar structure. The hydrophilic gadolinium hydroxide nanosheets have uniform size distribution, stable crystal structure, good dispersibility, simple preparation process, mild reaction conditions, less by-products, high yield, low equipment requirements and short preparation cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a flow chart of the present invention.
[0029] Figure 2 The figure is a schematic diagram of the preparation route of the hydrophilic gadolinium hydroxide nanosheets in the present invention.
[0030] Figure 3 The schematic diagram is a structural diagram of the silane coupling agents used in the present invention: 3-aminopropyltriethoxysilane (KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), and 3-(trihydroxysilyl)-propanesulfonic acid (SIT8378.3).
[0031] Figure 4 The XRD comparison diagram of the gadolinium oxide nanoparticles, the surface-modified gadolinium oxide nanoparticles and the hydrophilic gadolinium hydroxide nanosheets in the present invention is shown in FIG.
[0032] Figure 5 The figure is a comparison diagram of Fourier transform infrared spectra of gadolinium oxide particles, surface-modified gadolinium oxide nanoparticles and hydrophilic gadolinium hydroxide nanosheets in the present invention.
[0033] Figure 6 The scanning electron microscope image (left a) and the transmission electron microscope image (right b) of the hydrophilic gadolinium hydroxide nanosheets of the present invention are shown.
[0034] Figure 7 The figure is a comparison chart of the dispersion stability of the gadolinium oxide nanoparticles, the surface-modified gadolinium oxide nanoparticles and the hydrophilic gadolinium hydroxide nanosheets in water in the present invention.
[0035] Figure 8 The figure is a comparison diagram of the water contact angles of the gadolinium oxide nanoparticles, the surface-modified gadolinium oxide nanoparticles and the hydrophilic gadolinium hydroxide nanosheets in the present invention.
[0036] Fig. 91 is a zeta potential diagram of the gadolinium oxide particles, surface-modified gadolinium oxide nanoparticles and hydrophilic gadolinium hydroxide nanosheets in the present invention. DETAILED DESCRIPTION
[0037] The present invention will be described in detail below in conjunction with the accompanying drawings.
[0038] Embodiment 1:
[0039] See also Figure 1 , Figure 2 , a hydrophilic gadolinium hydroxide nanosheet, comprising 33.3% of gadolinium oxide nanoparticles and 66.7% of a silane coupling agent by mass percentage.
[0040] A method for preparing hydrophilic gadolinium hydroxide nanosheets comprises the following steps:
[0041] Step 1: Add 1 g of gadolinium oxide nanoparticles into 30 mL of deionized water and sonicate for 30 min to obtain a milky white dispersion A;
[0042] Step 2: Weigh 2 g of 3-aminopropyltriethoxysilane (KH-550), add 15 mL of deionized water to dilute, and obtain a 3-aminopropyltriethoxysilane (KH-550) solution. Add 30 g of the milky white dispersion A prepared in step 1 to the 3-aminopropyltriethoxysilane (KH-550) solution, and stir magnetically for 12 hours at a temperature of 20 ° C and a speed of 300 rpm to obtain liquid B. The structural diagram of the silane coupling agent 3-aminopropyltriethoxysilane (KH-550) is shown in FIG. Figure 3 ;
[0043] Step 3: Transfer the B solution prepared in step 2 to a dialysis bag with a molecular weight of 3500, dialyze for 12 hours, change the water every 3 hours, change the water 4 times, dialyze off the excess coupling agent on the surface, i.e., silane coupling agent 3-aminopropyltriethoxysilane (KH-550), and obtain the dialyzed B solution. Take 48g of the dialyzed B solution and transfer it to 35g of pretreated 732 strong acid styrene cation exchange resin. At a temperature of 20°C and a rotation speed of 300rpm, stir magnetically for 12 hours, filter out the 732 strong acid styrene cation exchange resin, and obtain clarified hydrophilic gadolinium hydroxide nanosheets.
[0044] The pretreatment operation steps of the 732 strong acid styrene cation exchange resin in step three are as follows: weigh 35g of the cation exchange resin, wash it with deionized water for 3 times, then measure 25mL of 4% hydrochloric acid solution or sulfuric acid solution or nitric acid solution by mass percentage and immerse and stir for 12h to obtain the pretreated 732 strong acid styrene cation exchange resin, convert the cation exchange resin from Na type to H type, which can adsorb a large amount of sodium ions present in liquid B, reduce the generation of by-products, and improve the yield.
[0045] Embodiment 2:
[0046] See also Figure 1 , Figure 2 , a hydrophilic gadolinium hydroxide nanosheet, comprising 35.7% of gadolinium oxide nanoparticles and 64.3% of a silane coupling agent by mass percentage.
[0047] A method for preparing hydrophilic gadolinium hydroxide nanosheets comprises the following steps:
[0048] Step 1: Add 1.5 g of gadolinium oxide nanoparticles into 35 mL of deionized water and sonicate for 45 min to obtain a milky white dispersion A;
[0049] Step 2: Weigh 2.7 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), add 20 mL of deionized water to dilute, to obtain a γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560) solution, adjust the pH to 6 with 0.5 mol / L NaOH solution or KOH solution or 0.5-2 mol / L NH3·H2O, and add 36.5 g of the milky white fraction prepared in step 1. Liquid A was added to a solution of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH-560) at a pH of 7, and the mixture was stirred for 24 h at a temperature of 25°C and a rotation speed of 400 rpm, so that γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH-560) fully wrapped the gadolinium oxide nanoparticles to obtain liquid B; the structural diagram of the silane coupling agent γ-(2,3-epoxypropyloxy)propyltrimethoxysilane is shown in FIG. Figure 3 ;
[0050] Step 3: The B solution prepared in step 2 is transferred to a dialysis bag with a molecular weight of 5000, dialyzed for 36 hours, the water is changed every 6 hours, and the water is changed 6 times. After dialyzing off the excess coupling agent silane coupling agent 3-aminopropyltriethoxysilane (KH-550) on the surface, the dialyzed B solution is obtained, 59.2 g of the dialyzed B solution is taken and transferred to 38 g of pretreated 732 strong acid styrene cation exchange resin, at a temperature of 25 ° C and a rotation speed of 400 rpm, magnetic stirring is performed for 24 hours, and the 732 strong acid styrene cation exchange resin is filtered out to obtain clarified hydrophilic gadolinium hydroxide nanosheets.
[0051] The pretreatment operation steps of 732 strong acid styrene cation exchange resin in step 3 are as follows:
[0052] Weigh 38g of 732 strong acid styrene cation exchange resin, wash it with deionized water for 3 times, then measure 30mL of 4.5% hydrochloric acid solution or sulfuric acid solution or nitric acid solution and immerse and stir for 24h to obtain the pretreated 732 strong acid styrene cation exchange resin, which can convert the cation exchange resin from Na type to H type, and can absorb a large amount of sodium ions in liquid B, reduce the generation of by-products, and improve the yield.
[0053] Embodiment three:
[0054] See also Figure 1 , Figure 2 , a hydrophilic gadolinium hydroxide nanosheet, comprising 40.0% of gadolinium oxide nanoparticles and 60.0% of a silane coupling agent by mass percentage.
[0055] A method for preparing hydrophilic gadolinium hydroxide nanosheets comprises the following steps:
[0056] Step 1: Add 2 g of gadolinium oxide nanoparticles into 40 mL of deionized water and sonicate for 60 min to obtain a milky white dispersion A;
[0057] Step 2: Weigh 3 g of 3-(trihydroxysilyl)-propane sulfonic acid (SIT8378.3), add 25 mL of deionized water to dilute, to obtain a 3-(trihydroxysilyl)-propane sulfonic acid (SIT8378.3) solution, adjust the pH to 7.5 using a 2 mol / L NaOH solution or KOH solution or NH3·H2O solution, add 42 g of the milky white dispersion A prepared in step 1 to the 3-(trihydroxysilyl)-propane sulfonic acid (SIT8378.3) solution with a pH of 6, and stir magnetically for 36 hours at a temperature of 28°C and a rotation speed of 600 rpm to allow the 3-(trihydroxysilyl)-propane sulfonic acid (SIT8378.3) to fully wrap the gadolinium oxide nanoparticles to obtain a solution B; the structural schematic diagram of 3-(trihydroxysilyl)-propane sulfonic acid (SIT8378.3) is shown in FIG. Figure 3 ;
[0058] Step 3: Transfer the liquid B prepared in step 2 to a dialysis bag with a molecular weight of 5000, dialyze for 48 hours, change the water every 8 hours, change the water 6 times, dialyze off the excess 3-(trihydroxysilyl)-propane sulfonic acid (SIT8378.3) on the surface, and obtain the dialyzed liquid B. Take 70g of the dialyzed liquid B and transfer it to 40g of pretreated 732 strong acid styrene cation exchange resin. At a temperature of 28°C and a rotation speed of 600rpm, stir magnetically for 36 hours, filter out the 732 strong acid styrene cation exchange resin, and obtain clarified hydrophilic gadolinium hydroxide nanosheets.
[0059] The steps of pretreatment of the 732 strong acid styrene cation exchange resin in step three are as follows: weigh 40 g of the 732 strong acid styrene cation exchange resin, wash it with deionized water for 3 times, then measure 35 mL of a 5% hydrochloric acid solution or a sulfuric acid solution or a nitric acid solution, immerse and stir for 16 hours, and obtain the pretreated 732 strong acid styrene cation exchange resin, that is, convert the cation exchange resin from Na type to H type, which can absorb a large amount of sodium ions in liquid B, reduce the generation of by-products, and improve the yield.
[0060] Embodiment 4:
[0061] See also Figure 1 , Figure 2 , a hydrophilic gadolinium hydroxide nanosheet, comprising 32.4% of gadolinium oxide nanoparticles and 67.6% of a silane coupling agent by mass percentage.
[0062] A method for preparing hydrophilic gadolinium hydroxide nanosheets comprises the following steps:
[0063] Step 1: Add 1.2 g of gadolinium oxide nanoparticles into 32 mL of deionized water and sonicate for 35 min to obtain a milky white dispersion A;
[0064] Step 2: Weigh 2.5 g of 3-aminopropyltriethoxysilane (KH-550), add 17 mL of deionized water to dilute, and obtain a 3-aminopropyltriethoxysilane (KH-550) solution. Add 33.2 g of the milky white dispersion A prepared in step 1 to the diluted 3-aminopropyltriethoxysilane (KH-550) solution, and stir magnetically for 18 hours at a temperature of 23 ° C and a speed of 350 rpm to obtain liquid B. The structural diagram of the silane coupling agent 3-aminopropyltriethoxysilane (KH-550) is shown in FIG. Figure 3 .
[0065] Step 3: Transfer the B solution prepared in step 2 to a dialysis bag with a molecular weight of 3500, dialyze for 20 hours, change the water every 4 hours, change the water 5 times, dialyze off the excess coupling agent on the surface, i.e., silane coupling agent 3-aminopropyltriethoxysilane (KH-550), and obtain the dialyzed B solution. Take 49.7 g of the dialyzed B solution and transfer it to 36 g of pretreated 732 strong acid styrene cation exchange resin. At a temperature of 23° C. and a rotation speed of 400 rpm, stir magnetically for 18 hours, filter out the 732 strong acid styrene cation exchange resin, and obtain clarified hydrophilic gadolinium hydroxide nanosheets.
[0066] The pretreatment operation steps of the 732 strong acid styrene cation exchange resin in step three are as follows: weigh 36g of the cation exchange resin, wash it with deionized water for 3 times, then measure 27mL of 5.5% hydrochloric acid solution or sulfuric acid solution or nitric acid solution by mass percentage, immerse and stir for 18h, and obtain the pretreated 732 strong acid styrene cation exchange resin, convert the cation exchange resin from Na type to H type, which can absorb a large amount of sodium ions in liquid B, reduce the generation of by-products, and improve the yield.
[0067] Embodiment five:
[0068] See also Figure 1 , Figure 2 , a hydrophilic gadolinium hydroxide nanosheet, comprising 38.3% of gadolinium oxide nanoparticles and 61.7% of a silane coupling agent by mass percentage.
[0069] A method for preparing hydrophilic gadolinium hydroxide nanosheets comprises the following steps:
[0070] Step 1: Add 1.8 g of gadolinium oxide nanoparticles into 38 mL of deionized water and sonicate for 50 min to obtain a milky white dispersion A;
[0071] Step 2: Weigh 2.9 g of 3-aminopropyltriethoxysilane (KH-550), add 23 mL of deionized water to dilute, and obtain a 3-aminopropyltriethoxysilane (KH-550) solution. Add 39.8 g of the milky white dispersion A prepared in step 1 to the diluted 3-aminopropyltriethoxysilane (KH-550) solution, and stir magnetically for 36 hours at a temperature of 28 ° C and a speed of 500 rpm to obtain liquid B. The structural schematic diagram of the silane coupling agent 3-aminopropyltriethoxysilane (KH-550) is shown in FIG. Figure 3 .
[0072] Step 3: Transfer the B solution prepared in step 2 to a dialysis bag with a molecular weight of 5000, dialyze for 36 hours, change the water every 6 hours, change the water 6 times, dialyze off the excess coupling agent on the surface, i.e., silane coupling agent 3-aminopropyltriethoxysilane (KH-550), and obtain the dialyzed B solution. Take 65.7 g of the dialyzed B solution and transfer it to 39 g of pretreated 732 strong acid styrene cation exchange resin. At a temperature of 28° C. and a rotation speed of 500 rpm, stir magnetically for 36 hours, filter out the 732 strong acid styrene cation exchange resin, and obtain clarified hydrophilic gadolinium hydroxide nanosheets.
[0073] The pretreatment operation steps of the 732 strong acid styrene cation exchange resin in step three are as follows: weigh 39g of the cation exchange resin, wash it with deionized water for 3 times, then measure 33mL of 6% hydrochloric acid solution or sulfuric acid solution or nitric acid solution by mass percentage, immerse and stir for 20h, and obtain the pretreated 732 strong acid styrene cation exchange resin, convert the cation exchange resin from Na type to H type, which can absorb a large amount of sodium ions present in liquid B, reduce the generation of by-products, and improve the yield.
[0074] See also Figure 4 It can be seen from the X-ray diffraction diagram that the gadolinium oxide nanoparticles with silane coupling agent grafted on the surface still maintain the same characteristic peaks as the gadolinium oxide nanoparticles at 2θ of 28°, 33°, 48° and 57°, while the modified gadolinium oxide nanoparticles after passing through the cation exchange resin show characteristic peaks of gadolinium hydroxide at 2θ of 17°, 27° and 29°, respectively. These characteristic peaks correspond to the (100), (110) and (101) crystal planes of gadolinium hydroxide, respectively, indicating that the gadolinium oxide dispersion grafted with silane coupling agent will become a gadolinium hydroxide solution after passing through the cation exchange resin; and the amorphous peak appearing at 2θ of 20° of the hydrophilic gadolinium hydroxide nanosheets prepared by the present invention is due to the coating of the surface of the gadolinium oxide nanoparticles by organic matter, indicating that the surface of the gadolinium oxide nanoparticles has been successfully modified by the silane coupling agent.
[0075] See also Figure 5, are attenuated total reflection Fourier infrared spectra of gadolinium oxide nanoparticles, gadolinium oxide nanoparticles surface-modified with a silane coupling agent, and hydrophilic gadolinium hydroxide nanosheets prepared by the present invention after being treated with a cation exchange resin. It can be seen that the infrared spectrum of the gadolinium oxide nanoparticles modified with a silane coupling agent 3-aminopropyltriethoxysilane (KH-550) shows a peak at 1050 cm -1 There is a strong Si-O bond stretching vibration peak on the left and right, as well as a peak at 1200 cm -1 The CN absorption peaks at 3450 cm-1 indicate that 3-aminopropyltriethoxysilane (KH-550) has been successfully grafted onto the surface of gadolinium oxide nanoparticles in the form of covalent bonds by hydrolysis. -1 A broad and intense OH vibration peak appears nearby, indicating that the hydrophilic gadolinium hydroxide nanosheets prepared by the present invention have been successfully prepared.
[0076] See also Figure 6 , which are scanning electron microscope (left a) and transmission electron microscope (right b) images of hydrophilic gadolinium hydroxide nanosheets. It can be seen that the hydrophilic gadolinium hydroxide nanosheets prepared in the present invention are thin sheet structures with large lateral dimensions and no agglomeration.
[0077] See also Figure 7 , which is a comparison chart of the dispersion stability of gadolinium oxide nanoparticles, surface-modified gadolinium oxide nanoparticles and hydrophilic gadolinium hydroxide nanosheets prepared by the present invention in water for 24 hours. The gadolinium oxide nanoparticles (left) will quickly agglomerate and precipitate in the aqueous solution, and obvious precipitation will appear at the bottom after standing for 24 hours. The aqueous solution of the surface-modified gadolinium oxide nanosheets modified with 3-aminopropyltriethoxysilane (KH-550) will also have a small amount of precipitation at the bottom. The aqueous solution of the hydrophilic gadolinium hydroxide nanosheets modified with a silane coupling agent and then treated with a cation exchange resin does not show any aggregation and precipitation, and has excellent stability, indicating that the gadolinium hydroxide nanosheets have good dissolution stability.
[0078] See also Figure 8 By comparing the water contact angles of the gadolinium oxide nanoparticles before and after treatment, the modified gadolinium oxide nanoparticles and the hydrophilic gadolinium hydroxide nanosheets prepared by the present invention, it can be seen that the water contact angles of the gadolinium oxide nanoparticles are 74.10° and 74.44°, the water contact angles of the modified gadolinium oxide nanoparticles are 83.33° and 83.46°, and the water contact angles of the hydrophilic gadolinium hydroxide nanosheets prepared by the present invention are 9.46° and 10.68°. It can be seen that the water contact angle of the hydrophilic gadolinium hydroxide nanosheets prepared by the present invention is significantly reduced. This is because the gadolinium hydroxide with a lamellar structure has greater wettability to water, and the weaker interaction force between the gadolinium layers makes the surface have a greater charge and a stronger polarity, thereby enhancing its hydrophilicity.
[0079] See also Fig. 9 , which is the ZETA potential analysis diagram, it can be seen that the potential of gadolinium oxide nanoparticles is about -12.5, the potential of modified gadolinium oxide nanoparticles is about 5, and the potential of hydrophilic gadolinium oxide nanosheets is about -20. It can be seen that after treatment with cation exchange resin, the absolute value of the ZETA potential of the formed gadolinium hydroxide nanosheets is larger than that of gadolinium oxide, and the dispersion stability of the system is enhanced.
[0080] In the above example, gadolinium oxide (Gd2O3, 99.99%), 3-aminopropyltriethoxysilane (KH-550) (C9H 23 NO3Si, 99.99%), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (C9H 20 O5Si, 97%), 3-(trihydroxysilyl)-propanesulfonic acid (SIT8378.3) (C3H 10 O6SSi), 732 strong acid styrene cation exchange resin (AR, sodium type) were purchased from MacLean Biochemical Technology Co., Ltd.
[0081] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the above embodiments, or replace some of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. The parts not described in detail in the present invention are well-known technologies for those skilled in the art.
Claims
1. A method for preparing hydrophilic gadolinium hydroxide nanosheets, characterized in that: The following steps are involved: Step 1: Mix gadolinium oxide nanoparticles and water in a mass ratio of 1: (20-30), and perform ultrasonic treatment for 30-60 minutes to obtain a milky white dispersion A; Step 2: diluting a silane coupling agent in deionized water to obtain a silane coupling agent solution, maintaining the pH of the silane coupling agent solution in the range of 6-7.5, adding the milky white dispersion A prepared in step 1 to the silane coupling agent solution, in a mass ratio of silane coupling agent: deionized water: milky white dispersion A = 1: (6.8-8.4): (13.2-15.5), at a temperature of 20-30° C. and a rotation speed of 300-600 rpm, magnetically stirring for 12-48 hours, so that the silane coupling agent fully wraps the gadolinium oxide nanoparticles to obtain liquid B; Step 3: Transfer the B solution prepared in step 2 to a dialysis bag with a molecular weight of ≥3000, dialyze for 12-48 hours, change the water 4-8 times in the middle, transfer the dialyzed B solution to the pretreated cation exchange resin, and the mass ratio of dialyzed B solution: cation exchange resin = 1: (0.57-0.78), at a temperature of 20-30° C. and a rotation speed of 300-600 rpm, stir magnetically for 12-48 hours, filter out the cation exchange resin, and obtain clarified hydrophilic gadolinium hydroxide nanosheets; The pretreatment process is as follows: weigh the cation exchange resin, clean the impurities with deionized water, immerse it in an acid solution with a mass percentage concentration of 4%-6% and stir it for 12-24 hours, and calculate the mass ratio of cation exchange resin: acid solution = 1: (0.71-1.21) to obtain the pretreated cation exchange resin, that is, convert the Na type cation exchange resin into the H type cation exchange resin.
2. The method for preparing a hydrophilic gadolinium hydroxide nanosheet according to claim 1, characterized in that: The cation exchange resin pretreated in step 3 is 732 strong acid styrene cation exchange resin.
3. The method for preparing a hydrophilic gadolinium hydroxide nanosheet according to claim 1, characterized in that: The silane coupling agent in step 2 includes 3-aminopropyltriethoxysilane or γ-(2,3-epoxypropoxy)propyltrimethoxysilane or 3-(trihydroxysilyl)-propanesulfonic acid.
4. The method for preparing a hydrophilic gadolinium hydroxide nanosheet according to claim 1, characterized in that: In the step 2, the pH of the solution is maintained in the range of 6-7.5, and the pH is adjusted by using 0.5-2 mol / L NaOH solution, 0.5-2 mol / L KOH solution, or 0.5-2 mol / L NH3·H2O solution.
5. The method for preparing a hydrophilic gadolinium hydroxide nanosheet according to claim 1, characterized in that: The acid solution includes hydrochloric acid solution, sulfuric acid solution or nitric acid solution.
Citation Information
Patent Citations
Method and installation for eliminating metal cations from liquid with polyazacloalkane resins grafted on support
CN1371305A
process AND INSTALLATION FOR THE ELIMINATION OF METALLIC CATIONS FROM A LIQUID BY POLYAZACYCLOALKANE RESINS GRAFTED ON A SUPPORT
FR2797786A1